Development and Validation of HPTLC Method along with Forced Degradation Study for the Simultaneous Estimation of Azelastine Hydrochloride and Fluticasone Propionate in Nasal Spray Formulation using Design of Experiment Approach - Patel, Kalpana Govindbhai; Patel, Seena Ghanshyam Kumar; Shah, Purvi Apurva; Tandel, Devang Bhagvandas; Gandhi, Tejal Ricky (Indian Journal of Pharmaceutical Education and Research, 2020)
Objectives: The present research study focuses on the development of the highperformance thin layer chromatographic method using design of experiment approach for the simultaneous estimation of Azelastine hydrochloride and Fluticasone propionate along with forced degradation study. Methods: High performance thin layer chromatographic separation was performed on aluminium plates precoated with silica gel 60 F254 using toluene: chloroform: methanol (5: 4: 2, v/v/v) as optimized mobile phase. Azelastine hydrochloride and Fluticasone propionate were exposed to different forced degradation conditions. Full factorial design was applied on acid and base induced degradation and statistical analysis by ANOVA was performed with interpretation of various plots. The method was validated by determination of linearity, precision, accuracy, specificity and robustness according to ICH guidelines. Results: From different forced degradation conditions, major degradation was observed in acidic and basic condition. Rf for Azelastine hydrochloride and Fluticasone propionate was 0.33 and 0.53 at 232 nm. The factor, temperature showed maximum % contribution in acid and base induced degradation. Linear concentration range was 280-1680 ng/band for Azelastine hydrochloride, 100-600 ng/band for Fluticasone propionate. The % recovery ranged within 101.15- 102.65% for Azelastine hydrochloride and 99.09-103.40% for Fluticasone propionate. The % R.S.D values were less than 2% for both drugs indicating that the method is accurate, sensitive and precise. Conclusion: In summary, a novel, simple, accurate and reproducible high-performance thin layer chromatographic method was developed, for routine quality control testing of pharmaceutical formulation.
Keywords: Azelastine Hydrochloride; Fluticasone Propionate; HPTLC; Degradation; DoE; (Design of experiment); Validation